LEXICAL LEVEL IN STYLISTIC ANALYSIS - Akhnazarov Abdulazizbek Boyxo’roz o’g’li; Zilola Abdurakhmanova Yoqubjon qizi (Ta'lim innovatsiyasi va integratsiyasi, 2023)
Abstract: In the realm of linguistics, the study of stylistics opens the door to the intricate artistry of language usage. Among its various levels, the lexical level stands as a pillar, showcasing the profound impact of word choice on the aesthetic, emotional, and communicative dimensions of a text. This article embarks on a journey through the fascinating terrain of lexical analysis, exploring how the selection and arrangement of words contribute to the unique stylistic fingerprint of a piece of writing. The Lexical Level Defined: At its essence, the lexical level of stylistic analysis focuses on the study of words—specifically, the choices made by authors in selecting and employing them. The richness and diversity of a language come to life through the lexicon, and understanding the stylistic implications of these choices provides valuable insights into the author's intent and the overall impact on the reader.